Covenant, blood, and violence: America at war with itself and others. Issue 1 (4th March 2019) - Peters, Ted
Abstract: Religious nationalism is dangerous, because it tends toward violence. In the case of America, religious nationalism is preceded by, and dependent upon, a covenant with God that renders judgment against the nation when it fails to embody divine justice. The second use of the law in Lutheran theology, combined with René Girard's scapegoat theory, provides the prophetic public theologian with a searchlight to make visible the nation's justification of violence. The haunting question becomes this: should the prophetic public theologian expose the lie on which American religious nationalism is built and risk sundering human community?